The Culture of French Revolutionary Diplomacy In the Face of Europe - Frey, Linda (Studies in Diplomacy and International Relations, 2018)
This book examines the culture of the French diplomatic corps from 1789 to 1799. It analyzes how the French revolutionaries attempted, albeit unsuccessfully, to transform the diplomatic culture of the old regime, notably in etiquette, language and dress and how the ideology and dynamic of the Revolution affected certain aspects of international affairs. Linda Frey is Professor of History at the University of Montana, US Marsha Frey is Professor of History at Kansas State University, US.